2021
DOI: 10.1021/acsomega.1c03363
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Natural Product Derived Macromolecules Based Interpenetrating Polymer Network for Therapeutic Drug Targeting

Abstract: Interpenetrating polymer network (IPN)-based bead formulations were exploited by cross-linking different hydrophilic polymers in different combinations and at different ratios. Polyvinyl alcohol, xanthan gum, guar gum, gellan gum, and sodium alginate (Na-alginate) were used in this work as hydrophilic polymers to enhance the solubility of diclofenac sodium and also to target the delivery at preferred locations. IPN beads based on polysaccharides were prepared by the ionic gelation method. Differential scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Therefore, the shape of calcium alginate gels depended on the viscosity of the sodium alginate solution (32) . Also the SEM approved drug loading as the empty beads ( Figure 9-a) showed rough surface, while the loaded beads ( Figure 9-b) showed smooth surface with crystalline fibers, which may be resulted from interaction of PRD with alginate and this result confirmed the FTIR results (19,31,33) .…”
Section: Semsupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, the shape of calcium alginate gels depended on the viscosity of the sodium alginate solution (32) . Also the SEM approved drug loading as the empty beads ( Figure 9-a) showed rough surface, while the loaded beads ( Figure 9-b) showed smooth surface with crystalline fibers, which may be resulted from interaction of PRD with alginate and this result confirmed the FTIR results (19,31,33) .…”
Section: Semsupporting
confidence: 66%
“…Table (2) showed that addition of hydrophilic polymer (F6-F9) increased the percentage yield and drug loading compared to F1. This may be due to presence of the polymer that caused higher viscosity of S. Alg hydrogel, preventing loss of the drug and generated a dense internal structure with white and uniform shape of beads as shown in figure (2) (19,20) .…”
Section: Effect Of Addition Of Hydrophilic Polymers To Sodium Alginat...mentioning
confidence: 99%
“…However, some drawbacks in terms of performance, such as thermal, moisture barrier, and mechanical properties, limit the polysaccharides application domain. To overcome these disadvantages and enhance the physicochemical properties and functional features of polysaccharides, several effective strategies, including cross-linking, blending with other natural or synthetic polymers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], or incorporation of antioxidant agents, e.g., phenolic compounds [ 13 , 14 , 15 , 21 , 22 , 23 , 24 , 25 , 26 ] have been proposed. For instance, blending of CS with natural or synthetic polymers, including xylan [ 24 ], starch [ 25 ], poly(vinylalcohol) (PVA) [ 26 ], or polyethylene terephthalate [ 27 ], has been reported to improve the mechanical properties of the composite films.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant examples, prepared for potential use in drug delivery systems, are exemplified in Table 6. In general terms, the formation of second-generation IPNs (with poorer mechanical properties than those of the third generation) is usually conducted either by the mixture of two natural polymers [28,29] or by the mixture of a natural polymer and a hydrophilic synthetic macromolecule such as poly(vinyl alcohol) (PVA) [28,30], which cross-links reversibly. The third-generation IPNs present improved mechanical properties since Polymer 2 grows in the colloidal suspension of Polymer 1, which guarantees a more homogeneous intertwined structure of the final material [35].…”
Section: Discussionmentioning
confidence: 99%